2018
DOI: 10.3389/fmicb.2018.00127
|View full text |Cite
|
Sign up to set email alerts
|

Does Treatment Order Matter? Investigating the Ability of Bacteriophage to Augment Antibiotic Activity against Staphylococcus aureus Biofilms

Abstract: The inability to effectively treat biofilm-related infections is a major clinical challenge. This has been attributed to the heightened antibiotic tolerance conferred to bacterial cells embedded within biofilms. Lytic bacteriophages (phages) have evolved to effectively infect and eradicate biofilm-associated cells. The current study was designed to investigate the ability of phage treatment to enhance the activity of antibiotics against biofilm-forming Staphylococcus aureus. The biofilm positive S. aureus stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 37 publications
(53 reference statements)
7
95
0
Order By: Relevance
“…They are able to degrade biofilm matrix, thereby enhancing the efficacy of antibiotics and reducing the concentration of antibiotics required to eradicate infection (13,14). Recent studies have demonstrated that phages can eradicate biofilms by their synergistic action with antibiotics (15,16).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…They are able to degrade biofilm matrix, thereby enhancing the efficacy of antibiotics and reducing the concentration of antibiotics required to eradicate infection (13,14). Recent studies have demonstrated that phages can eradicate biofilms by their synergistic action with antibiotics (15,16).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…Lysogenized phage P1 in E. coli showed PAS in the presence of ciprofloxacin, and a P1 Ref endonuclease amplified the lytic cycle when a bacterial SOS response was induced by DNA damage (11). A synergistic effect was also observed when removing P. aeruginosa and S. aureus biofilms (12,13). The degree of synergy depended upon the specific antibiotic used (14).…”
mentioning
confidence: 99%
“…A similar effect was also observed for vancomycin and ciprofloxacin. The promising potential of the phage-antibiotic staggered treatment has been recently highlighted by other two groups (14, 15), and may be related to the potential antagonistic effect of simultaneous treatment with antibiotics, which inhibit and/or kill bacteria, and bacteriophages, which require replicating bacterial cells to propagate (33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Ryan et al showed that a synergistic effect of cefotaxime was observed when used in combination with the T4 phage against Escherichia coli biofilm (13). Two independent studies also demonstrated that pre-treating Pseudomonas aeruginosa (14) and S. aureus (15) biofilms with bacteriophages before antibiotic administration determined a major reduction of bacterial viability compared to the effect observed with the simultaneous administration of these therapeutic agents. However, none of the above-mentioned papers investigated the mechanisms through which phages can enhance antibiotics activity against biofilms.…”
Section: Introductionmentioning
confidence: 99%